Mediating Role of Competitive Advantage on the Relationship of Supply Chain Management and Organizational Performance on the Food Industry of Thailand - Jatturong Ploenhad; Pornpanna Laoprawatchai; Chairit Thongrawd; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
This study evaluated the effectiveness of supply chain management (SCM) practices with respect to competitive advantage and firm performance. It also investigated the mediating role of competitive advantage between SCM practices and organizational performance relationships. It used the PLS-SEM to examine the association between the variables under study. Data were collected form the supply chain mangers of the food industry in Thailand. The results indicated that effective practices of SCM could increase the competitive advantage and organizational performance. This study also revealed that the competitive advantage of the firm mediates the SCM practices and organizational performance relationship.